La Plata y Le Corbusier - Arrese, Álvaro
Análisis sobre la Casa Curutchet.
Keywords: LE CORBUSIER; ARGENTINA; BUENOS AIRES (PROV); LA PLATA; VIVIENDAS; VIVIENDAS UNIFAMILIARES; VIVIENDAS CON ESTUDIO; CRITICA